Solar radiation characteristics at Qena / Egypt - EL-SHAZL, SAYED M.; ABDELMAGEED, Y.A.M.; EL-NOUBI ADAM, M. (MAUSAM, 1998)
Measurements of the hourly global solar radiation (G) and its diffuse component (D) on a horizontal surface have been carried out in Qena / Upper Egypt in the period from June 1992 to May 1993. The corresponding diffuse fraction (DIG) is calculated. Diurnal variations of the results have been studied. Also the daily totals values and its monthly and seasonal averages as well as their frequency distributions were computed and examined. The seasonal and climatic effects on the fluctuation of the results are discussed. These effects were particularly large during spring and Winter months owing to the high fluctuation of the atmospheric conditions with aspect to amount of clouds, water content, and concentration of aerosol dust particles. The influence of clouds is also considered. It shows small effect on the results (4.5%), reflecting the low degree of cloudiness in the study region. The relation between the diffuse fraction and clearness index (G/Go) shows that most of the points lies in the region of the high availability of the incoming solar radiation. In general the study shows clearly the abundance of solar energy in Qena / Egypt, and the suitability of its climate for using it in different applications.